(untitled) (Web of Teachers: Inderscience Research, 2025)
The development of critical thinking and problem-solving skills is essential for students in academic lyceums, where mathematical education plays a pivotal role in shaping intellectual capacity and analytical reasoning. This article explores the implementation of modern pedagogical approaches in teaching mathematics, including inquiry-based learning, collaborative problem-solving, and the integration of digital technologies. Emphasis is placed on how these methods foster deeper conceptual understanding, creativity, and independent thinking among students. The study also highlights the challenges faced by educators in adapting to innovative methodologies and suggests strategies for effective integration within the curriculum. Through qualitative and quantitative observations, the article demonstrates that modern teaching approaches significantly enhance students’ engagement, critical thinking abilities, and overall academic performance in mathematics.